On Z-open sets (Journal of the College of Basic Education, 2023)
Continuous real valued function is an important tool in topology. Inthis paper, real valued continuous functions are used to define some kind ofsets called zero sets which is the inverse image of zero of a real valuedfunction from a topological space, the complement of zero sets is called acozero sets, and the family of all cozero sets of a topological space X formsa base for a topology on X which is called the Z-topology on X and itselements is called Z-open sets.In this work we study the properties of these sets with some relationsbetween it and other sets like open, cozero and zero sets. On the other handwe proved some results and characterizations with some examples.